1 EFFECT OF MODERN MARKET EXISTENCE (MINIMARKET) ON STAPLE FOOD TRADER PERFORMANCE IN TRADITIONAL MARKETS - Lies Maria Hamza (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2018)
The aim of this study is to analyse whether there are differences in profitability, sales turnover, sales value growth, and the achievement of sales targets between staple food traders which are near and far from minimarket. This study used primary data through questionnaires and interviews to forty-eight respondents. From the test results obtained that there are differences in the level of profitability, sales turnover, sales value growth, profit growth, achievement of significant sales targets between staple food stores which are near and far from minimarket.